2020
DOI: 10.3390/ijms21145137
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of JAK Inhibitor on the Survival, Anagen Re-Entry, and Hair Follicle Immune Privilege Restoration in Human Dermal Papilla Cells

Abstract: Topical or systemic administration of JAK inhibitors has been shown to be a new treatment modality for severe alopecia areata (AA). Some patients show a good response to JAK inhibitors, but frequently relapse after cessation of the treatment. There have been no guidelines about the indications and use of JAK inhibitors in treating AA. The basic pathomechanism of AA and the relevant role of JAK inhibitors should support how to efficiently use JAK inhibitors. We sought to investigate the effect of JAK1/2 inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 22 publications
0
20
0
1
Order By: Relevance
“…We also found that the IFN-γ-induced proinflammatory cytokines and chemokines of AA ( Figure 3 ) were suppressed by MSCT in hORSCs [ 37 , 38 ]. Due to the inflammatory response, these molecules disrupt the immune privilege of HFs, induce dystrophic change and catagen, and prevent anagen re-entry.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…We also found that the IFN-γ-induced proinflammatory cytokines and chemokines of AA ( Figure 3 ) were suppressed by MSCT in hORSCs [ 37 , 38 ]. Due to the inflammatory response, these molecules disrupt the immune privilege of HFs, induce dystrophic change and catagen, and prevent anagen re-entry.…”
Section: Discussionmentioning
confidence: 97%
“…We previously studied the efficacy of MSCT in hDPCs, one of the key cells that make up the hair bulge [ 37 ]. There are similarities and differences between the results of that study and the results of the current research.…”
Section: Discussionmentioning
confidence: 99%
“…The drug increased the expression of some growth factors, and also inhibited the phosphorylation of JAK1, JAK2, JAK3, STAT1 and STAT3. Study results suggest that ruxolitinib therapy may prevent interferon gamma-induced hair loss [39].…”
Section: Il-15mentioning
confidence: 94%
“…The impact of JAK/STAT inhibitors on the inductive capacity of hDP cells was showed when tofacitinibtreated hDP spheroids displayed improved HF induction rate than those treated with ruxolitinib, which performed similarly to non-treated spheroids 69 . The treatment with tofacitinib upregulated TGF-β2, BMP6, and LEF1 expression 69 whilst ruxolitinib improved β-catenin gene expression but decrease TGF-β2 expression 70 . This suggests a TGF-β2 mediated hair growth after inhibition of the JAK/STAT signaling pathway.…”
Section: Mesenchymal Cellsmentioning
confidence: 99%